Molecular mechanisms of epithelial-barrier disruption by Helicobacter pylori. - Wessler, Silja; Backert, Steffen (Trends in Microbiology, 2008)
Intact intercellular junctions and cell-matrix contacts are important structures in the formation and maintenance of epithelial-barrier functions against microbes. The human gastric pathogen Helicobacter pylori developed a remarkable network of strategies to alter these epithelial cell-cell and cell-matrix adhesions, which are implicated in inflammation, proliferation, cell migration and invasive growth. This review focuses on recent findings on H. pylori-induced host-cell signaling. We propose a stepwise model for how H. pylori interacts with components of focal adhesions and intercellular tight and adherens junctions to disrupt the epithelial layer, providing novel insights into the pathogenesis of H. pylori.